Effect of magnesium addition on the microstructure and properties of ductile Ni-resist alloy using in-mould magnesium treatment method - Mohd Rashidi, Maarof (2015)
For engineering reasons, ductile Ni-resist alloys are widely used in oil and gas, automotive industries and elevated temperature purposes. Ductile Ni-resist offers an advantage because this alloy has an austenitic structure at all temperatures. However, ductile Ni-resist alloy faces economical limitation due to the high price of nickel for alloying of ductile Ni-resist. Therefore, the present study aims to explore the possibility to reduce nickel consumption by substituting nickel with manganese to generate austenitic structure of ductile Ni-resist. Austenitic structure was formed by adding a nickel with much higher manganese percentage consumption as compared to standard usage. The control of carbide formation due to increasing Mnlwt. % was conducted using inoculation method. The effect on solidification was evaluated using cooling curve thermal analysis, complemented by microscopic observation and mechanical properties. It was observed that both Mn/wt. % and inoculation affect the austenitic structure and solidification cooling curve. Solidification cooling curve was lowered with increasing Mn/wt. %.It was also observed that graphite microstructure can be modified by both Mn/wt. % and inoculation. The morphology and graphite distribution was affected by increasing Mri/wt. % and inoculation. An isolated region due to segregation known as 'Last To Freeze' was the last area to solidify. Tensile strength and elongation at room temperature dropped by 21.5% (12Mn-lONi wt %) and 20.0% respectively as compared to D2 standard alloys. Tensile strength at elevated temperature showed that this alloy can withstand up to 150 MPa, dropped by 6.15% (12Mn-lONi wt. %) compared to D2 standard alloy. Corrosion test proved that corrosion rate is comparable to unmodified ductile Ni-resist. Three dense oxide layers were formed on the alloy surface at elevated temperature. A good agreement was observed between the result of the solidification cooling curve, microstructure and mechanical properties.